Trends in Research on the NISWATHI Coaching Model with LMS for Science Teacher Pedagogy and Professionalism - Ni Nengah Sri Swathi; A Wahab Jufri; AA Sukarso; I Putu Artayasa; Joni Rokhmat (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Science education faces significant challenges, particularly in relation to the limited pedagogical competence and professionalism of teachers, as well as the underutilization of digital technology in learning. This research aims to explore trends in the implementation of the NISWATHI coaching model assisted by a Learning Management System (LMS) in enhancing science teacher competencies. The study employed a bibliometric and content analysis design based on 1,000 documents indexed in Google Scholar. Data were collected using Publish or Perish and Dimensions.ai with keywords related to coaching, LMS, and teacher professionalism. The selection of data followed the PRISMA protocol through stages of identification, screening, and quality assessment, while VOSviewer was used for keyword mapping and visualization. The analysis revealed a significant increase in scientific publications related to the topic, peaking in 2022, with the majority appearing in book chapters, edited volumes, and conference proceedings. The dominant disciplines contributing to the literature were education, teacher training, and educational technology. The findings underline the importance of integrating digital technology, strengthening pedagogical competence, and fostering innovation in teacher training models. This study contributes theoretically by mapping the current state of research and practically by offering insights for policymakers and educators in developing effective professional development programs for science teachers.